Corporate Social Responsibility Reporting in Malaysia: A Research Note - Zainal, Dalilawati; Zainuddin, Suria (Asian Journal of Accounting Perspectives, 2013)
This study examines selected literature on Corporate Social Responsibility Reporting (CSRR) in Malaysia, as one of the important economies in Asia. A review of literature on CSRR revealed the importance of governance as a tool to promote Corporate Social Responsibility (CSR), thus impressing the greater importance of CSRR. Support from multiple stakeholders, particularly the government, regulatory authorities and shareholders, is needed as they can have a significant impact on a company’s operations. With the implementation of mandatory CSRR in Malaysia beginning from the financial year of 2007, appropriate reporting standards could be produced as a guideline for reporting CSR-related information. The enforcement of existing regulations is also needed to ensure the continuous development of CSR and CSRR in Malaysia. This calls for more research in the field of study to be conducted, specifically in Malaysia to provide an Asian perspective.